Schumann resonances at Mars: Effects of the day‐night asymmetry and the dust‐loaded ionosphere. Issue 2 (17th January 2017) - Toledo‐Redondo, S.; Salinas, A.; Portí, J.; Witasse, O.; Cardnell, S.; Fornieles, J.; Molina‐Cuberos, G. J.; Déprez, G.; Montmessin, F.
Abstract: Schumann resonances are standing waves that oscillate in the electromagnetic cavity formed between the conducting lower ionosphere and the surface of the planet. They have been measured in situ only on Earth and Titan, although they are believed to exist on other planets like Mars. We report numerical simulations of the Martian electromagnetic cavity, accounting for the day‐night asymmetry and different dust scenarios. It has been found that the resonances are more energetic on the nightside, the first resonance is expected to be 9–14 Hz depending on the dust activity and to have low quality factors ( Q ≃2). This work serves as an input for the upcoming Exomars surface platform (launch 2020), who will attempt to measure them for the first time. Key Points: Full 3‐D simulations of the Mars‐ionosphere cavity to study Schumann resonances Day‐night asymmetry on Mars modifies the global Schumann resonance patterns Martian dust conditions can modify Schumann resonances, first resonance variations between 9 and 14 Hz